Environmental laws, health, and impacts - Montemayor, Jose C. Jr. (Quezon City, Philippines : Central Book Supply, 2018)
The state of our environment has been deteriorating for centuries. Every part of the planet has been negatively impacted by man. Environmental degradation was greatly accelerated by the industrial revolution that took place in the 19th century.
Chapter 1. Introduction: health and the Environment -- Chapter 2. Climate Change and the Environment -- Chapter 3. Environmental Problems in the Philippines -- Chapter 4. International Agreements and laws on Environments and Climate Change -- Chapter 5. Right to a Healthy Environment -- Chapter 6. Environment Impacts -- Chapter 7. Environmental Assessment -- Chapter 8. Environmental Justice National and International -- Chapter 9. Non-Governmental Organization -- Chapter 10. People's Organizational -- Chapter 11. Health and environment.
Keywords: ENVIRONMENTAL LAW -- PHILIPPINES